(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Graph labeling is an assignment of integers to the vertices or edges or both subject to certain conditions. A graph ???? = (????, ????) with p vertices and q edges is said to admit sum divisor edge cordial labeling if the edge labeling h from E(G) to 1,2, . . . , ???? induces the mapping ℎ∗ from ????(????) to 0,1 as ℎ∗(????) is 1 if 2 is a divisor of Σ????????∈????(????) ℎ(????????) and 0 otherwise with the condition that the number of vertices having label 0 and the number of vertices having label 1 differ by at most 1. A graph with a sum divisor edge cordial labeling is called a sum divisor edge cordial graph. In this paper, we prove that path graph, complete bipartite graph, gear graph, wheel graph, helm graph, closed helm graph, friendship graph, fan graph and double fan graph are sum divisor edge cordial graphs.